2015
DOI: 10.1155/2015/624627
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A, Cancer Treatment and Prevention: The New Role of Cellular Retinol Binding Proteins

Abstract: Retinol and vitamin A derivatives influence cell differentiation, proliferation, and apoptosis and play an important physiologic role in a wide range of biological processes. Retinol is obtained from foods of animal origin. Retinol derivatives are fundamental for vision, while retinoic acid is essential for skin and bone growth. Intracellular retinoid bioavailability is regulated by the presence of specific cytoplasmic retinol and retinoic acid binding proteins (CRBPs and CRABPs). CRBP-1, the most diffuse CRBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 124 publications
0
91
0
3
Order By: Relevance
“…In addition, the RA pathway is defective in many cancers, including EOC [49]. To test whether PRAME expression is associated with altered RA signaling in EOC and HGSC, we used Gene Set Enrichment Analysis (GSEA) to test the relationship between PRAME mRNA expression and RA-mediated gene expression in a large set of published EOC ( N = 285) and HGSC ( N = 218) expression data [50].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the RA pathway is defective in many cancers, including EOC [49]. To test whether PRAME expression is associated with altered RA signaling in EOC and HGSC, we used Gene Set Enrichment Analysis (GSEA) to test the relationship between PRAME mRNA expression and RA-mediated gene expression in a large set of published EOC ( N = 285) and HGSC ( N = 218) expression data [50].…”
Section: Resultsmentioning
confidence: 99%
“…However, they cannot be synthesized de novo by animals (including human) and must be obtained from the diets11. Recently, a myriad of epidemiological studies have demonstrated an inverse relationship between dietary vitamin A consumption and cancer development12. For instance, vitamin A has been proved to play a protective role in breast cancer13 and lung cancer14.…”
mentioning
confidence: 99%
“…CRBP-1 suppression is associated with a more aggressive phenotype in breast, ovary, and nasopharyngeal cancer. Overexpression of CRBP-1 increases the sensitivity to retinol and reduces the viability of ovarian cancer cells in vitro [51].…”
Section: Discussionmentioning
confidence: 99%